2021
DOI: 10.3390/nu13072186
|View full text |Cite
|
Sign up to set email alerts
|

Graph Theory-Based Electroencephalographic Connectivity and Its Association with Ketogenic Diet Effectiveness in Epileptic Children

Abstract: Ketogenic diet therapies (KDTs) are widely used treatments for epilepsy, but the factors influencing their responsiveness remain unknown. This study aimed to explore the predictors or associated factors for KDTs effectiveness by evaluating the subtle changes in brain functional connectivity (FC) before and after KDTs. Segments of interictal sleep electroencephalography (EEG) were acquired before and after six months of KDTs. Analyses of FC were based on network-based statistics and graph theory, with a focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Betweenness centrality is a measure of centrality in a graph based on the shortest paths in graph theory. Research has shown that nodes with high betweenness centrality are potential hubs for surgical resection [ 31 ], and may be used as an indicator to monitor seizure reduction after ketogenic diet therapy in childhood epilepsy [ 32 ]. Betweenness centrality might indicate localized connectivity and potentially plays a protective role in seizure spread or recurrence [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betweenness centrality is a measure of centrality in a graph based on the shortest paths in graph theory. Research has shown that nodes with high betweenness centrality are potential hubs for surgical resection [ 31 ], and may be used as an indicator to monitor seizure reduction after ketogenic diet therapy in childhood epilepsy [ 32 ]. Betweenness centrality might indicate localized connectivity and potentially plays a protective role in seizure spread or recurrence [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that nodes with high betweenness centrality are potential hubs for surgical resection [ 31 ], and may be used as an indicator to monitor seizure reduction after ketogenic diet therapy in childhood epilepsy [ 32 ]. Betweenness centrality might indicate localized connectivity and potentially plays a protective role in seizure spread or recurrence [ 32 ]. Our results showed decreased function of betweenness centrality in the theta, alpha, and beta frequency bands in BECTS patients with seizures, but not in those without clinical seizures compared to controls, and might indicate weaker local connectivity in BECTS patients with clinical seizures.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a 30% reduction in the IED index in sleep EEG data after 6 weeks of KDT was associated with good KDT effectiveness [ 10 ]. In our previous work, we proposed graph theory-based EEG functional connectivity as a feasible approach to monitoring the effectiveness of KDT in children with epilepsy [ 11 ]. However, it should be noted that researchers have yet to reach a consensus as to the benefits of KDT.…”
Section: Introductionmentioning
confidence: 99%